Убийство царской семьи - Платонов О. А. (Сов. Россия, 1991)
Экземпляры: аб (ретроконверсия) / Инвентарный номер: 31587 / Цена: 2.43 / Сис.шифр: 63.3(2).711 / Авт.знак: П37 / ГРНТИ: 03 / ББК: 63.3(2).711